Light composite scalar boson from a see-saw mechanism in two-scale TC models - Doff, A.; Natale, A. A. [UNESP] (Elsevier, 2015)
We consider the possibility of a light composite scalar boson arising from mass mixing between a relatively light and heavy scalar singlets in a see-saw mechanism expected to occur in two-scale Technicolor (TC) models. A light composite scalar boson can be generated when the TC theory features two technifermions species in different representations, R1 and R2, under a single technicolor gauge group, with characteristic scales Λ1 and Λ2. We determine the final composite scalar fields, Φ1 and Φ2, effective theory using the effective potential for composite operators approach. To generate a light composite scalar it is enough to have a walking (or quasi-conformal) behavior just for one of the technifermions representations.
Keywords: General properties of QCD (dynamics, confinement); Other nonperturbative techniques; Technicolor models